2012
DOI: 10.1198/jcgs.2011.09128
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Working Correlation Structure in Generalized Estimating Equations via Empirical Likelihood

Abstract: Generalized estimating equations (GEE) are a popular class of models for analyzing discrete longitudinal data, and do not require the specification of a full likelihood. The GEE estimator for the regression parameter will be the most efficient if the working correlation matrix is correctly specified. Hence it is desirable to choose a working correlation matrix that is the closest to the underlying structure among a set of working structures. In the absence of a parametric likelihood, traditional likelihood-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…In this case, we can more efficiently estimate cov ( Y i ) within the empirical covariance matrix with φAi12RUAi12 rather than ( Y i − μ i ) ( Y i − μ i ) T , i = 1, … , N , thus possibly enhancing the selection performances of criteria. For instance, Chen and Lazar proposed criteria based upon empirical likelihood versions of the AIC and BIC, which performed better than the CIC and QIC in their simulation study. However, their criteria assume correctly specified working marginal variances and a common correlation structure, which was only as general as the stationary structure in their simulation study.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we can more efficiently estimate cov ( Y i ) within the empirical covariance matrix with φAi12RUAi12 rather than ( Y i − μ i ) ( Y i − μ i ) T , i = 1, … , N , thus possibly enhancing the selection performances of criteria. For instance, Chen and Lazar proposed criteria based upon empirical likelihood versions of the AIC and BIC, which performed better than the CIC and QIC in their simulation study. However, their criteria assume correctly specified working marginal variances and a common correlation structure, which was only as general as the stationary structure in their simulation study.…”
Section: Discussionmentioning
confidence: 99%
“…Until results from future research, currently whether one set of M and L choice is better than the others is still not yet known. Choice of working correlation structures of the methods may be based on prior information or scientific consideration, as well as many existing methods such as CIC (Hin and Wang, ), QIC (Pan, ), and the empirical AIC and BIC (Chen and Lazar, ). If prior or scientific information is available, it may be preferable to use this information to choose working correlation structure, but even in this case it may be desirable to also compare the results with those based on CIC, QIC, and empirical AIC/BIC as sensitivity analysis, since such sensitivity analysis may provide additional insights.…”
Section: Discussionmentioning
confidence: 99%
“…The author indicated that the covariates were first selected based on QIC, and the variance function could be identified as the one minimizing EQIC given the selected covariates; then "working" correlation structure selection could be achieved based on CIC; in addition, they found out that the covariates selection by EQIC given different working variance functions was more consistent than that based on QIC [45]. Besides those criteria mentioned above, Cantoni et al also discussed the covariate selection for longitudinal data analysis [46]; also, a variance function selection was mentioned by Pan and Mackenzie [30] as well as Wang and Lin [47]; in addition, more work on "working" correlation structure selection was addressed by Chaganty and Joe [48], Wang and Lin [47], Gosho et al [49,50], Jang [51], Chen [52], and Westgate [53][54][55], among others. Overall, the model selection of GEE is nontrivial, where the best selection criterion is still being pursued [56], and the recent work by Wang et al can be followed up as the rule of thumb [45].…”
Section: Methodsmentioning
confidence: 99%